1996
DOI: 10.1163/22941932-90000637
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Robinetin Crystals in Vessels of Intsia Species

Abstract: Many samples of Intsia spp. contain a few vessels which, throughout their length, possess some elements filled with bright yellow crystals. They serve as a characteristic of the genus. An examination was undertaken to elucidate the mode of formation of these crystals, which have been identified as pure robinetin, and the factors which may control their presence. It was concluded they are formed at pit membranes inside these particular vessels. The non-structural components of fibres, parenchyma and vessels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 6 publications
3
6
0
Order By: Relevance
“…The substance in pit membranes (Figure 10 w5x) was also kaempferol-3-rhamnoside, as its spectrum showed the typical maxima at 270 and 350 nm. Accordingly, the hypotheses of Hillis (1996) that synthesis of the deposits in afzelia and merbau is regulated by pit membraneassociated enzymes was confirmed in this study. The extractives (Figure 10 w2x) situated in the S2 of vessels of afzelia are also characterised by absorbance spectra with maxima around 280 nm and slight shoulders at 340 nm owing to the presence of UV-active conjugated double bonds.…”
Section: Figure 10supporting
confidence: 81%
See 2 more Smart Citations
“…The substance in pit membranes (Figure 10 w5x) was also kaempferol-3-rhamnoside, as its spectrum showed the typical maxima at 270 and 350 nm. Accordingly, the hypotheses of Hillis (1996) that synthesis of the deposits in afzelia and merbau is regulated by pit membraneassociated enzymes was confirmed in this study. The extractives (Figure 10 w2x) situated in the S2 of vessels of afzelia are also characterised by absorbance spectra with maxima around 280 nm and slight shoulders at 340 nm owing to the presence of UV-active conjugated double bonds.…”
Section: Figure 10supporting
confidence: 81%
“…ence of chromophore groups, such as conjugated double bonds, attributed to highly condensed phenolics, as previously described for discoloured beech wood (Koch et al 2003;Koch 2004). It can be confirmed that deposits in the pit membranes are of pure robinetin, as already assumed by Hillis (1996Hillis ( , 1998. It can be confirmed that deposits in the pit membranes are of pure robinetin, as already assumed by Hillis (1996Hillis ( , 1998.…”
Section: Figure 10supporting
confidence: 64%
See 1 more Smart Citation
“…Although assumed to be minor, there is a possibility in species with pit membrane remnants (see Table 2) for potential ‘hydrogel’ effects resulting from using pure water rather than an ionic solution for measurements (Zwieniecki, Melcher & Holbrook 2001a). Crystals or other debris could accumulate on scalariform plates under measurement conditions or potentially in vivo (crystals have been observed within vessels (Scurfield & Mitchell 1973; Hillis 1996), resulting in an increased flow resistance. Occlusion of plates might have been responsible for the three statistical outliers in vessel resistivity.…”
Section: Discussionmentioning
confidence: 99%
“…It is dark reddish-brown. Hillis (1996) mentioned the colour of water soluble material (extractives) from heartwood of Merbau as dark brown. When it infiltrated during impregnation to Jabon wood of cream colour, the colour of the treated Jabon wood (T1 and T2) was in between the colour of the untreated wood and the original colour of Merbau extractives.…”
Section: Evaluation On Colour Changesmentioning
confidence: 99%